A review on municipal solid waste as a renewable source for waste-to-energy project in India: Current practices, challenges, and future opportunities. (20th December 2020) - Chand Malav, Lal; Yadav, Krishna Kumar; Gupta, Neha; Kumar, Sandeep; Sharma, Gulshan Kumar; Krishnan, Santhana; Rezania, Shahabaldin; Kamyab, Hesam; Pham, Quoc Bao; Yadav, Shalini; Bhattacharyya, Suparna; Yadav, Virendra Kumar; et al.
Abstract: Waste generation is steadily growing in developing countries such as India due to the continuous growth of industrialization, urbanization, and population. Mismanagement of municipal solid waste (MSW) not only has negative environmental effects but also causes the risk to public health and raises some other socio-economic issues that are worth discussions. Therefore, it is essential to urgently enhance the handling of waste collection, segregation, and safe disposal. Waste-to-energy (WtE) technologies such as pyrolysis, gasification, incineration, and biomethanation can convert MSW, as an appropriate source of renewable energy, into useful energy (electricity and heat) in safe and eco-friendly ways. This review aims at (1) describing the challenges of MSW management, (2) summarizing the health significance of MSW management, (3) explaining the opportunities and requirements of energy recovery from MSW through WtE technologies, (4) explaining several WtE technologies in detail, and (5) discussing the current status of WtE technologies in India. The paper also discusses the challenges to WtE projects in India. Moreover, a number of recommendations are provided for improving the currently implemented solid waste management (SWM) in the Indian context. This review has the potential of helping scholars, researchers, authorities, and stakeholders working on MSW management to make effective decisions. Highlights: Municipal solid waste management (MSW) is a serious environmental problem in India. MSW can be used as a renewable source of energy through various waste-to-energy (WtE) technologies. A total of 138.3 MW of WtE capacity has been installed in India as on 31st March 2019. WtE can produce a significant amount of energy from waste thus reduce the issue of MSW management.